Functional properties of traditional frozen and sun-dried products of oca (Oxalis tuberosa Molina) and olluco (Ullucus tuberosus Caldas): A review - Chuquilín Goicochea, Roberto Carlos (2020)
The objective was to understand the importance of two organic Andean tubers such as Oxalis tuberosa Molina and Ullucus tuberosus Caldas, in terms of its components beneficial to human health and to add value by an ancient technique, commonly called "chuño" known as caya and chullce in the Huancavelica region. Science direct, Taylor & Francis, Wiley, PubMed, Scielo and Alicia databases were reviewed, with an age of 20 years. The most relevant results were systematized in tables and analyzed to highlight the qualities that both tubers have as a fresh product, and the possibilities that they may have when converting them into agro-industrial products that retain their functional properties.